ABO blood group and the risk of lung cancer in Greek adults: a case — control study - Chrysanthakopoulos, N.A.; Dareioti, N.S. (Experimental Oncology, 2018)
Aim: The present study aimed to investigate any possible association between ABO blood groups and lung cancer. Materials and Methods: The study was conducted on 122 lung cancer patients and 1,255 matched-healthy individuals that were reviewed retrospectively. Chi-square and logistic regression models were used for statistical analysis. Results: No significant difference between lung cancer patients and the control group was recorded regarding ABO blood types and the risk of lung cancer (p = 0.055, OR = 0.79, 95% CI 0.61–1.03). Male gender (p = 0.006, OR = 2.08, 95% CI 1.24–3.49) and smoking (p = 0.000, OR = 3.13, 95% CI 1.72–5.69) were significantly associated with the risk of lung cancer. Conclusion: No association between ABO blood types and the risk of lung cancer was observed. Key Words: ABO blood types, lung cancer, adults, risk factor.